2001
DOI: 10.1002/hec.652
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal screening for cystic fibrosis: an economic analysis

Abstract: Cystic fibrosis (CF) is the most common life-shortening genetically transmitted disease in Denmark with a birth prevalence of 1 in 4700, resulting in 12-15 new cases of cystic fibroses annually. The aim of this study is to disclose the societal resource implications of introducing a population wide prenatal screening programme for cystic fibrosis in Denmark. The present analysis is limited to the monetary consequences of introducing a screening programme, where costs of screening are compared to the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 18 publications
2
15
0
1
Order By: Relevance
“…Duchenne muscular dystrophy) were associated with an increased number of admissions and associated costs as patients became older. These data are consistent with other studies [24,25] and with the natural history of these disorders, which have a greater impact on morbidity with increasing age [26]. In contrast, admissions due to DS and polydactyly show a decreasing trend in admissions in older children and adolescents, also consistent with the course and management of these disorders [27,28].…”
Section: Discussionsupporting
confidence: 81%
“…Duchenne muscular dystrophy) were associated with an increased number of admissions and associated costs as patients became older. These data are consistent with other studies [24,25] and with the natural history of these disorders, which have a greater impact on morbidity with increasing age [26]. In contrast, admissions due to DS and polydactyly show a decreasing trend in admissions in older children and adolescents, also consistent with the course and management of these disorders [27,28].…”
Section: Discussionsupporting
confidence: 81%
“…Pilot studies in pregnant women and couples in Europe obtained slightly higher uptake rates (76–91%) than in the U.S., but similar termination rates (14/14) [56,57,58,59,60,61,62]. In contrast, studies done in couples with a family history of CF in Europe found higher termination rates among family members than the Wisconsin study.…”
Section: Resultsmentioning
confidence: 70%
“…7,10,12,34 It also compares favorably with the cost per CF case detected via prenatal screening in the US (US$400,000 -$500,000 for non-Hispanic Caucasians and Ashkenazi Jewish), 34 and Denmark. 35 However, making similar cost comparisons for lives with TSD avoided would be more contentious than it is for CF; being untreatable and so rapidly fatal, lives with TSD may be relatively much less medically costly than lives with CF, but the severity of mental and physical effects (in the child affected and their parents) should, arguably, make the value of preventing TSD births much higher. This highlights the major problem, facing all evaluations of programs that have multiple objectives, of how to relatively "weight" the value of knowing genetic carrier status for different disorders.…”
Section: Discussionmentioning
confidence: 99%